Ultrafast assembly of swordlike Cu3(1, 3, 5-benzenetricarboxylate)n metal–organic framework crystals with exposed active metal sites. Issue 7 (23rd April 2020) - Ahmed, Heba; Yang, Xinci; Ehrnst, Yemima; Jeorje, Ninweh N.; Marqus, Susan; Sherrell, Peter C.; El Ghazaly, Ahmed; Rosen, Johanna; Rezk, Amgad R.; Yeo, Leslie Y.
Abstract : A new acoustomicrofluidic method for synthesizing copper-based metal–organic frameworks is shown to yield novel large aspect ratio elongated crystal morphologies with high active metal site density on their surfaces, leading to enhanced conductivity. Abstract : Owing to their large surface area and high uptake capacity, metal–organic frameworks (MOFs) have attracted considerable attention as potential materials for gas storage, energy conversion, and electrocatalysis. Various strategies have recently been proposed to manipulate the MOF surface chemistry to facilitate exposure of the embedded metal centers at the crystal surface to allow more effective binding of target molecules to these active sites. Nevertheless, such strategies remain complex, often requiring strict control over the synthesis conditions to avoid blocking pore access, reduction in crystal quality, or even collapse of the entire crystal structure. In this work, we exploit the hydrodynamics and capillary resonance associated with acoustically-driven dynamically spreading and nebulizing thin films as a new method for ultrafast synthesis of swordlike Cu3 (1, 3, 5-benzenetricarboxylate) n (Cu–BTC) MOFs with unique monoclinic crystal structures ( P 21 / n ) distinct to that obtained via conventional bulk solvothermal synthesis, with 'swordlike' morphologies whose lengths far exceed their thicknesses. Through pulse modulation and taking advantage of the rapid solvent evaporation associated with the high nebulisation rates, we are also able to control the thicknesses of these large aspect ratio (width and length with respect to the thickness) crystals by arresting their vertical growth, which, in turn, allows exposure of the metal active sites at the crystal surface. An upshot of such active site exposure on the crystal surface is the concomitant enhancement in the conductivity of the MOF, evident from the improvement in its current density by two orders of magnitude.